1986
DOI: 10.1073/pnas.83.6.1709
|View full text |Cite
|
Sign up to set email alerts
|

Bovine parathyroid cells: cultures maintained for more than 140 population doublings.

Abstract: Primary cultures of bovine parathyroid cells were developed using Coon's modified Ham's F-12 medium containing low (0.3 mM) concentrations of calcium and supplements of bovine hypothalamic extract, bovine pituitary extract, epidermal growth factor, insulin, transferrin, selenous acid, hydrocortisone, triiodothyronine, retinoic acid, and galactose. These cells were cultured serially on serum-coated dishes for 140 population doublings before signs of senescence were detected. The cells were epithelioid and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…After 24 h in culture, CaR mRNA and protein are present only in very low concentrations on the PT cells in primary culture, and at later time intervals, not present at all. There have been studies in a cell line derived from rat PT showing that Ca 2ϩ regulates PT cell proliferation (11) and there are changes in cyclin D1 mRNA, not cyclin D2 and D3, after changes in medium Ca 2ϩ concentration (7). Sakaguchi et al (62,63) showed that these cells expressed acidic fibroblast growth factor (aFGF) and expression of both aFGF mRNA and peptide was suppressed by calcium.…”
Section: Pt Cell Proliferationmentioning
confidence: 99%
“…After 24 h in culture, CaR mRNA and protein are present only in very low concentrations on the PT cells in primary culture, and at later time intervals, not present at all. There have been studies in a cell line derived from rat PT showing that Ca 2ϩ regulates PT cell proliferation (11) and there are changes in cyclin D1 mRNA, not cyclin D2 and D3, after changes in medium Ca 2ϩ concentration (7). Sakaguchi et al (62,63) showed that these cells expressed acidic fibroblast growth factor (aFGF) and expression of both aFGF mRNA and peptide was suppressed by calcium.…”
Section: Pt Cell Proliferationmentioning
confidence: 99%
“…Upon hypocalcemia, synthesis is markedly increased within 6 hours. This can hardly be explained by cell hyperplasia, since the cell cycle measured in vitro is approximately 20 hours (Brandi et al, 1986). In studies of long-term (3 weeks) hypocalcemia, a fivefold increase in PTH mRNA levels was observed despite high endogenous calcitriol levels, indicating a dominant effect of hypocalcemia on PTH synthesis (Naveh-Many and Silver, 1990).…”
Section: Hypocalcemiamentioning
confidence: 99%
“…Replacing serum in the culture medium by growth factors and other supplements allows extended culture of some cell types that cannot be maintained on a long-term basis in conventional serumcontaining media (Ambesi-Impiombato et al, 1980;Orly et al, 1980;Gospodarowicz et al, 1981;Hammond et al, 1984;Brandi et al, 1986). We have applied a similar serum-free approach to the culture of mouse embryo cells.…”
mentioning
confidence: 99%